2002
DOI: 10.1016/s0261-5606(02)00003-7
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate effects on the volume and variability of trade flows

Abstract: This paper investigates the effects of exchange rate uncertainty on the volume and variability of trade flows. Employing a signal extraction framework, we show t h a t the direction and magnitude of importers' and exporters' optimal trading activities depend upon the source of the uncertainty (general microstructure shocks, fundamental factors driving the exchange rate process, or a noisy signal of policy innovations), providing a rationale for the contradictory empirical evidence in the literature. W e also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 34 publications
1
58
0
1
Order By: Relevance
“…Chowdhury (1993), Arize (1995), and Choudhry (2001) report a negative impact, while Qian and Varangis (1994) and Baum et al (2002) find a negative effect for some countries and a positive for others. Doyle (2001) finds that in the case of Irish-UK trade positive effects predominate.…”
Section: Model Specificationmentioning
confidence: 98%
See 1 more Smart Citation
“…Chowdhury (1993), Arize (1995), and Choudhry (2001) report a negative impact, while Qian and Varangis (1994) and Baum et al (2002) find a negative effect for some countries and a positive for others. Doyle (2001) finds that in the case of Irish-UK trade positive effects predominate.…”
Section: Model Specificationmentioning
confidence: 98%
“…Coes (1981) uses a log-level specification to examine Brazilian exports 1 Empirical papers on the issue include, among many others, Kenen and Rodrik(1986), Cushman(1988), Qian and Varangis (1994), Lee(1999), Doyle(2001), and Baum et al (2002), while examples of theoretical contributions are Ethier (1973), Hooper andKohlhagen (1978), De Grauwe (1988), Baldwin and Krugman (1989), Viane and de Vries (1992), and Barkoulas et al (2002). Surveys of the literature can be found in Côté (1994) and McKenzie (1999).…”
Section: Introductionmentioning
confidence: 99%
“…4, No. 8 ISSN: 2222 227 www.hrmars.com Barkoulas et al (2002) examined the impact of exchange rate fluctuation on the volume and variability of trade flows. They concluded that, exchange rate volatility discourages expansion of the volume of trade thereby reducing its benefits.…”
Section: International Journal Of Academic Research In Business and Smentioning
confidence: 99%
“…Interestingly, there are also some studies that stay in the middle and propose an ambiguous impact of the exchange rate volatility on trade (e.g. Viaene & De Vries, 1992;Barkoulas et al, 2002) due to several reasons such as type of shocks on exporters.…”
Section: Introductionmentioning
confidence: 99%